(3QSGdI aj GdGOhjI GdeaQOIs - (3CHh YeQ GdcfOj , CHh jYbhH Hf eMeO Hf ESMGb GdcfOj, GdcfOj,J (B355 (3g` s
(3ChdgG (B:s
(3QSGdI djYbhH ai GdGOhjI GdeaQOI GdJi jaYd HNhGUgG ai GdSehe ef GdSehe GdbGJdI hLejY dPY GdOhGH s
(3BNQgG (B:s
(3faY ef LejY GdSehe GdbGJdI hEf CNP efg GdTF GdjSjQ hCVja eY TQGH QjMGfi JeJ HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdg GdMGOjI hGdKdGKhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B148 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B142s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs